Security Vulnerabilities of Virtualization Technique - N, Saravanan; A, Umamakeswari (International Journal of Engineering and Technology, 2018)
Cloud computing is a computing model for delivering resources in a convenient manner from a shared pool. The resources provisioned and released on an on-demand basis with minimal intervention of service provider. Cloud Computing is becoming the platform for all kind of web based services. Virtualization is the key concept to adopt the cloud computing. Virtualization offers many benefits comparing to real physical machine implementation infrastructure.Â Even though virtualization provides lots of benefits, it is also brings several security vulnerabilities. This paper presents the security breaches of various virtualization techniques that are applied in virtual machines, in which health care records maintained.Â